HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PASIEN GANGGUAN JIWA DI WILAYAH KERJA PUSKESMAS SICINCIN - Amira Esti; Sri Burhani Putri; Sevina Ulan Sari (Ensiklopedia of Journal, 2023)
According to WHO (2021) around 450 million people currently suffer from mental disorders, and nearly 1 million people commit suicide every year. The 2021 Ministry of Health report states that it is estimated that around 400 thousand people have mental disorders. Meanwhile, the report from the Sicincin Puskesmas, Padang Pariaman Regency in 2022 stated that the number of people with mental disorders was found to be 250 people, this figure has increased compared to 2021 which was recorded as many as 345 people. Patients who do not comply with medication or experience recurrent recurrences of the patient's condition will cause their condition to worsen and it is difficult to return to its original state. One of the obstacles in the effort to cure mental patients is the knowledge of the community and family. The research objective was to determine the relationship between knowledge and family support with adherence to taking medication for patients with mental disorders in the working area of the Sicincin Health Center. This research is a quantitative study using cross sectional method. This research was conducted in the working area of the Sicincin Public Health Center in February 2023. The study population was all families of mental disorders patients with samples taken by purposive sampling, obtained a sample of 75 people. The results of the study found that 66.7% of respondents have low knowledge, 53.3% have poor family support, 61.3% do not comply with taking medication. There is a significant relationship between knowledge and adherence to taking medication for mental disorders with a p value of 0.001. There is a significant relationship between family support and adherence to taking medication for people with mental disorders with a p value of 0.001Keywords : Knowledge, Family Support, Compliance with Medication